Encyclopedia Brown gets his man - Sobol, Donald J., 1924-; Shortall, Leonard (New York : T. Nelson, 1967)
Ten brief cases in which the reader pits his wits against those of Encyclopedia Brown, an ingenious twelve-year-old detective
Keywords: Detective and mystery stories